2022
DOI: 10.3389/fonc.2022.786438
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Survey of Genomic Mutations in Breast Cancer Reveals Recurrent Neoantigens as Potential Therapeutic Targets

Abstract: Neoantigens are mutated antigens specifically generated by cancer cells but absent in normal cells. With high specificity and immunogenicity, neoantigens are considered as an ideal target for immunotherapy. This study was aimed to investigate the signature of neoantigens in breast cancer. Somatic mutations, including SNVs and indels, were obtained from cBioPortal of 5991 breast cancer patients. 738 non-silent somatic variants present in at least 3 patients for neoantigen prediction were selected. PIK3CA (38%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 42 publications
4
12
0
Order By: Relevance
“…Our results showed that SNV is the most abundant variant type with C>T being the most abundant SNV type in both BRCA1 -positive and -negative groups. This corresponds with the study results by Zhou and colleagues in 5991 unspecified breast cancer samples [ 32 ]. Mutational burden represented by total variant counts showed differences between BRCA1 -positive and -negative among all databases with the BRCA1 -positive group harboring more SNVs and indels compared to the BRCA1 -negative group.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results showed that SNV is the most abundant variant type with C>T being the most abundant SNV type in both BRCA1 -positive and -negative groups. This corresponds with the study results by Zhou and colleagues in 5991 unspecified breast cancer samples [ 32 ]. Mutational burden represented by total variant counts showed differences between BRCA1 -positive and -negative among all databases with the BRCA1 -positive group harboring more SNVs and indels compared to the BRCA1 -negative group.…”
Section: Discussionsupporting
confidence: 92%
“…TP53 and PIK3CA were found mutated in 30.24–37.39% and 30.08–39.48% of all BRCA1 -negative samples, respectively. These mutational frequencies are similar to the findings in unspecified breast cancer samples ( TP53 37%; PIK3CA 38%) [ 32 , 42 ]. In the BRCA1 -positive group, however, TP53 was found to be the top mutated gene with much higher frequencies of 59.09–75.00% of all BRCA1 -positive samples.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…A total of 2 of the 10 predicted peptides stimulated T cells to secrete IFNγ and were cytotoxic to autologous tumor cells, suggesting the presence of neoantigen-specific T cells, which may be suitable vaccine targets. In another study designed to identify a neoantigen signature for breast cancer, Zhou et al integrated mutational data from 8 published cohorts of close to 6000 breast cancer patients [ 20 ]. Interestingly, they found that four mutations (3 from PIK3CA and 1 from AKT1), predicted to be restricted by HLA alleles common in Han Chinese and Americans, were identified in 2.5–14% of the samples.…”
Section: Introductionmentioning
confidence: 99%